Higher Education for Global and Local Sustainable Development - O. V. Zinevich; E. A. Melekhina (Высшее образование в России)
The Russian universities’ contribution to the achievement of sustainable development goals is analyzed from the prospect of globalism crisis and transition to the global-local paradigm of the existence of a society. The authors proceed from the theoretical premise that the internationally recognized threefold concept of sustainable development encompassing economic development, social stability and environmental sustainability is based on the understanding of the development as a process and a result of subjective and objective factors that effective in activity aimed at building the future of the humankind. Sociocultural approach allows considering the universities’ practices on achieving global goals of sustainable development through local (national and cultural) practices: ecological, economical and socially oriented activity and/ or building ecosystems at a local level. The article is aimed to define the universities’ organizational environment and conditions providing the high level of sustainable development goals’ achievement.Universities implement various strategies to introduce the concept of sustainability into the programs of their development. The practices of the universities known for the effective implementation of sustainability concept into educational, research and social practices oriented to the regional sustainable development are analyzed. The universities under consideration provide stimulating ground for establishing horizontal and vertical relationships among all subjects of sustainable development within their educational environment, fostering sustainability culture and motivating students, teachers and other personnel to achieve sustainability goals. Their experience might be informative for Russian Universities as far as the principles of sustainable development and orientation at building educational ecosystems are formulated in the national programs of regional development in Russia (Flagship Universities Program and Priority 2030 Program). In the Priority 2030 Program, the ecosystem principle is one of the fundamental for the result-oriented innovative development of regional clusters created by the joint efforts of universities, businesses, state and social organizations. However, Russian universities in their striving for designing educational ecosystem mostly focus on research and financial aspects than on the development of a man, whose professional, intellectual and moral formation might contribute to the sustainable development of the region, the nation and the world.